2019
DOI: 10.1016/j.bios.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Emerging neurotechnology for antinoceptive mechanisms and therapeutics discovery

Abstract: The tolerance, abuse, and potential exacerbation associated with classical chronic pain medications such as opioids creates a need for alternative therapeutics. Phenotypic screening provides a complementary approach to traditional target-based drug discovery. Profiling cellular phenotypes enables quantification of physiologically relevant traits central to a disease pathology without prior identification of a specific drug target. For complex disorders such as chronic pain, which likely involves many molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 156 publications
(162 reference statements)
0
28
0
Order By: Relevance
“…MEAs enable non-invasive, thus repeatable, recordings of extracellular action potentials. Although recordings of random DRG cultures have been previously demonstrated (Black et al, 2019), these are not adapted to the study of peripheral innervation. Here, we employed microElectrode-microFluidic (μEF) devices (Figure 7A), which allowed us to monitor axonal activity with great fidelity (Figure 7B) (Heiney et al, 2019; Lopes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…MEAs enable non-invasive, thus repeatable, recordings of extracellular action potentials. Although recordings of random DRG cultures have been previously demonstrated (Black et al, 2019), these are not adapted to the study of peripheral innervation. Here, we employed microElectrode-microFluidic (μEF) devices (Figure 7A), which allowed us to monitor axonal activity with great fidelity (Figure 7B) (Heiney et al, 2019; Lopes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the few studies where neurons were seeded only in one compartment, the propagating event detection methods presumed orthodromic propagation from the somal to the axonal compartment (forward propagation) (Habibey et al, 2017; Lewandowska et al, 2016). It is important to note that no study has previously attempted to characterize the signal conduction of DRG cultures (Black et al, 2019). Still, preliminary in vitro experiments using DRGs had suggested that most APs propagate orthodromically (Heiney et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike mature hippocampal neurons, DRG neurons did not fire in bursts but rather exhibited sporadic spontaneous activity. In physiological conditions, this relatively low level of activity also occurs in vivo (Black et al, 2019). As DRG explants were placed outside the MEA active area, activity was only recorded in the microchannels ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations